The combined effect of cardiorespiratory and muscular fitness on the incidence of metabolic syndrome before midlife - Kun‐Zhe Tsai; Chen‐Chih Chu; Wei‐Chun Huang; Xuemei Sui; Carl J. Lavie; Gen‐Min Lin (Wiley, 2024)
Abstract Background Cardiorespiratory fitness (CRF) could reduce the risk of metabolic syndrome (MetS) while the association between muscular endurance capacity (MEC) and incident MetS has rarely been investigated in young adults. Methods A total of 2890 military men and women, aged 18-39 years, free of baseline MetS in Taiwan, were followed for incident MetS from baseline (2014) until the end of 2020. All subjects received annual health examinations for assessment of MetS. Physical fitness was assessed by CRF (estimated maximal oxygen uptake, VO2 max [mL/kg/min], in a 3000‐m run) and MEC (numbers of 2‐min push‐ups). MetS was defined according to the International Diabetes Federation (IDF) criteria. Multiple Cox regression analysis was conducted with adjustments for baseline age, sex, substance use status and physical activity to determine the associations of CRF and MEC with incidences of new‐onset MetS and related features, for example, central obesity, hypertension, dyslipidaemia and prediabetes or diabetes. To examine the combined effects of CRF and MEC status on incidence of MetS, high and low levels of CRF and MEC were separately defined by over and under the sex‐specific median in each exercise test. Results During a median follow‐up of 5.8 years, there were 673 (23.3%) new‐onset MetS. Higher CRF was associated with a lower incidence of MetS (hazard ratio [HR] and 95% confidence interval: 0.905 [0.877-0.933]), and its components separately, except hypertension. No association was observed between MEC and incident MetS, and its components separately, except hypertension. When evaluating the combined effects of MEC and CRF status on the incidence of MetS, it was observed that compared with the low CRF/low MEC, the high CRF/high MEC (HR: 0.553 [0.439-0.697]) and the high CRF/low MEC (HR: 0.730 [0.580-0.918]) had a lower incidence of new‐onset MetS (P value for the intergroup difference = 0.04). There was no significant result for the low CRF/high MEC. Conclusions This study highlights that although the protective effects of MEC to reduce the incidence of MetS and most of its related features were mainly driven by CRF in young adults, there was an addictive effect of greater MEC on CRF to prevent the development of new‐onset MetS before midlife.